Solvent-Free Synthesis of α-Cyanophosphonates from β-Nitrostyrenes by Using a Deep-Eutectic Solvent Catalyst - Shamsaddinimotlagh, Sima; Ranjbari, Mohammad A.; Tavakol, Hossein; Shi, Min (Synlett, 2024)
α-Cyanophosphonates, which are useful reagents for the Horner–Wittig reaction, were synthesized under solvent-free conditions by using a choline chloride–zinc chloride deep-eutectic solvent (DES) as a catalyst. This is only the second report on the synthesis of these compounds. In the previous report, diethyl trimethylsilyl phosphite was used as a reagent and TiCl4 as a catalyst, whereas in this study, both the reagent (triphenylphosphine) and the catalyst (choline chloride–zinc chloride DES) are cheaper, more readily available, and less harmful than those used in the previous work. Moreover, the process involves an interesting cascade reaction between a β-nitrostyrene and two equivalents of triphenyl phosphite, leading to the desired product by a new synthetic route. The products can be used in the pharmaceutical and agricultural industries, in addition to their synthetic applications in the preparation of α,β-unsaturated nitriles. The reactions were completed on using 20 mol% of DES at 80 °C in six hours. Ten different β-nitrostyrenes were synthesized in yields of 55–87% after purification. β-Nitrostyrenes containing electron-donating groups showed higher yields. The reaction failed when aliphatic or heteroaromatic nitroalkenes or β-nitrostyrenes with electron-withdrawing substituents were employed. Finally, three plausible mechanistic routes are proposed for the reaction, starting with the nucleophilic addition of triphenyl phosphite to the carbon, nitrogen, or oxygen atom in the α-position.
Keywords: cyanophosphonates; choline chloride; deep-eutectic solvent; nitrostyrenes; triphenyl phosphite; organocatalysis